Viral dsRNA triggers human fetal membrane miR-146a-3p to be packaged into small extracellular vesicles which in turn drives inflammation through activation of Toll-like Receptor 7 and 8 - Hanah M. Georges; Abigail C. Fischer; Paloma Casanova; Vikki M. Abrahams (PLoS ONE, 2026)
Maternal infection and chorioamnionitis are one of the leading causes of preterm birth and neonatal morbidity. The relationship and mechanisms linking bacterial infections and preterm labor are well researched, however, less is known about the mechanisms involved in how viral infections contribute to preterm labor. Previous work from our group demonstrated that following bacterial triggers, fetal membranes (FMs) express elevated miR-146a-3p which in turn acts as an intermediate danger signal by activating TLR8 to induce a robust inflammatory response. Using an established FM explant model system, the role of this and other TLR7/8-activating miRs in the propagation of viral-induced inflammation was investigated. Following exposure to the viral dsRNA mimic and TLR3 agonist, Poly(I:C), expression of FM tissue TLR7/8-activating miRs (miR-146a-3p, miR-21a, miR-29a, and Let7b) were not elevated. Despite this, in response to Poly(I:C), elevated FM secretion of pro-inflammatory IL-6 and IL-8, and IL-1β was TLR7- and TLR8-dependent. To investigate alternative methods of miR delivery, small extracellular vesicles (sEVs) from FM supernatants were isolated and found to contain elevated levels of miR-146a-3p and miR-21a under Poly(I:C) conditions. Furthermore, Poly(I:C)-induced IL-6 and IL-8 responses were reduced in the presence of an inhibitor of sEV biogenesis/release, and IL-6 and IL-1β production was reduced in the presence of a miR-146a-3p inhibitor. Together, these data suggests that sEVs produced from virally-stimulated human FMs contain and deliver elevated miR-146a-3p which acts as a danger signal to drive perpetuate inflammation via TLR7 and TLR8 activation. This work demonstrates a novel and important role for sEV packaged TLR7/8 activating-miR-146a-3p in FM inflammatory responses to viral infections.